Enhancement of heat transfer in a circular tube with tangential swirl generators - Gül, H (Taylor & Francis Inc, 2006)
The effect of swirl flow on the heat transfer augmentation in a tube flow was studied experimentally. Swirl flow was generated at the entrance of the tube by tangential injectors. The injector angles to the tube axis were 45 degrees, 70 degrees, and 90 degrees. The heating was performed electrically and water was used as working fluid. The heat transfer coefficients in swirl flow were measured over a length of 100 cm from the tangential inlet. In the experiments, total mass flux was varied from 25.95 kg/m(2) sn to 1038 kg/m(2) sn and Reynolds number ranges from 4,800 to 25,000. The local heat transfer coefficients were found to increase to a very large value along downstream of the injection location, and then decrease with the distance (x/L). Experimental results confirmed that the use of tangentially injections leads to a higher heat transfer rate over the plain tube. The augmentation of heat transfer was found to be the function of the tangential to total flow momentum ratio and Reynolds number. No pronounced effect of injector number and angle on heat transfer was observed. The augmentation was from 60% to 28%, depend on M-t/M-T. The average Nusselt number was correlated in terms of Reynolds number and the ratio of the tangential momentum to axial momentum of the flow.
Keywords: tangential injection; swirl; heat transfer; flow